2015
DOI: 10.3389/fnins.2015.00156
|View full text |Cite
|
Sign up to set email alerts
|

The blood-brain barrier and methamphetamine: open sesame?

Abstract: The chemical and electrical microenvironment of neurons within the central nervous system is protected and segregated from the circulation by the vascular blood–brain barrier. This barrier operates on the level of endothelial cells and includes regulatory crosstalk with neighboring pericytes, astrocytes, and neurons. Within this neurovascular unit, the endothelial cells form a formidable, highly regulated barrier through the presence of inter-endothelial tight junctions, the absence of fenestrations, and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…[18] Besides, Meth decreases tyrosine hydroxylase and tryptophan hydroxylase activities [19,20] and increases astrocytic expression of basic fibroblast growth factor and glial fibril-lary acidic protein (GFAP) that are necessary for sensitization to amphetamine. [21] Lastly, Meth leads to metabolic alterations [22,23] and the degradation of the BBB, [14,24] triggering secondary injury to the neuronal cells. While the mechanism is still unclear, [24] Meth is known to affect BBB permeability [14,16,24] directly through inflammatory signaling that alters tight junctions and fluid-phase vesicular transport following glial activation, aminergic nerve damage, and hyperthermia, as well as by indirect mechanisms involving microglia activation and transmigrating leukocytes.…”
Section: The Functional State Of the Neurovascular Unit (Nvu) Composmentioning
confidence: 99%
“…[18] Besides, Meth decreases tyrosine hydroxylase and tryptophan hydroxylase activities [19,20] and increases astrocytic expression of basic fibroblast growth factor and glial fibril-lary acidic protein (GFAP) that are necessary for sensitization to amphetamine. [21] Lastly, Meth leads to metabolic alterations [22,23] and the degradation of the BBB, [14,24] triggering secondary injury to the neuronal cells. While the mechanism is still unclear, [24] Meth is known to affect BBB permeability [14,16,24] directly through inflammatory signaling that alters tight junctions and fluid-phase vesicular transport following glial activation, aminergic nerve damage, and hyperthermia, as well as by indirect mechanisms involving microglia activation and transmigrating leukocytes.…”
Section: The Functional State Of the Neurovascular Unit (Nvu) Composmentioning
confidence: 99%
“…Only a few of these studies controlled the effective plasma concentrations of METH during the observation period. 72 Various molecular pathways have been proposed and their cross talk implicates oxidative stress as a central pathogenic mechanism that may contribute to METH-induced endothelial dysfunction and BBB damage. 63,64,67,70 Importantly, METH challenge elicited an intense oxidative and inflammatory stress response by increased generation of ROS, pro-inflammatory cytokines, and depletion of inherent anti-oxidant systems (such as glutathione and related enzymes) in BBB endothelium.…”
Section: Meth Abuse and Blood-brain Barrier Dysfunctionmentioning
confidence: 99%
“…Our study showed that induction of BBB opening occurred with METH at low concentrations and thus compatible with relative safe use. Other reported METH treatment regimens employ much higher concentrations, which are demonstrably more neurotoxic in rodents and likely to be so in humans (also discussed in Turowski & Kenny, 2015). Furthermore, induction of transport-competent caveolae at the BBB offers clear advantages over opening paracellular junctions, the mechanism invoked of treatment regimens utilising higher METH concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Circulating METH leads to BBB breakdown in rodents (Martins et al, 2011;Turowski & Kenny, 2015). Based on this feature, METH has been proposed for use to enhance drug transport to the diseased brain (Kast, 2007).…”
Section: Introductionmentioning
confidence: 99%